Deep Democracy: Urban Governmentality and the Horizon of Politics. (May 2019) - Appadurai, Arjun
This paper describes the work of an alliance formed by three civic organisations in Mumbai to address poverty—the NGO SPARC, the National Slum Dwellers Federation and Mahila Milan, a cooperative representing women's savings groups.* It highlights key features of their work which include putting the knowledge and capacity of the poor and the savings groups that they form at the core of all their work (with NGOs in a supporting role); keeping politically neutral and negotiating with whoever is in power; driving change through setting precedents (for example, a community-designed and managed toilet, a house design developed collectively by the urban poor that they can build far cheaper than public or private agencies) and using these to negotiate support and changed policies (a strategy that develops new 'legal' solutions on the poor's own terms); a horizontal structure as the Alliance is underpinned by, accountable to and serves thousands of small savings groups formed mostly by poor women; community-to-community exchange visits that root innovation and learning in what urban poor groups do; and urban poor groups undertaking surveys and censuses to produce their own data about 'slums' which official policies lack and need) to help build partnerships with official agencies in ways that strengthen and support their own organisations. The paper notes that these are features shared with urban poor federations and alliances in other countries and it describes the international community exchanges and other links between them. These groups are internationalising themselves, creating networks of globalisation from below. Individually and collectively, they seek to demonstrate to governments (local, regional, national) and international agencies that urban poor groups are more capable than they in poverty reduction, and they also provide these agencies with strong community-based partners through which to do so. They are, or can be, instruments of deep democracy, rooted in local context and able to mediate globalising forces in ways that benefit the poor. In so doing, both within nations and globally, they are seeking to redefine what governance and governability mean.